Pharmaceutical Processing and Standardization of Modified Dosage Form of Jeevaneeyagana Kashaya as Spray Dried Powder Capsules - Parvathy Sunil; Rajam R (International Journal of Ayurveda and Pharma Research, 2024)
Jeevaneeyagana Kashaya is an Ayurvedic formulation that can be used for its preventive and therapeutic properties. However, its liquid dosage form has a limited shelf life and is difficult to administer. The present study works on standardizing and evaluating the Jeevaneeyagana Kashaya (JGK) extract capsules prepared using spray dryer technology, which consist of Withania somnifera, Asparagus racemosus, Pueraria tuberosa, Vigna trilobata, Teramnus labialis, Leptadaenia reticulata, and Glycyrrhiza glabra. The spray-dried extract was evaluated for phytochemical characters. Moreover, physical property analysis, such as bulk density, tapped density, compressibility index, and angle of repose for the formulated JGK extract capsules, was done. The capsules were evaluated for their organoleptic characters. Microbial load, heavy metal analysis, and disintegration time were also determined. The JGK extract capsule formulation complied with the assessed qualities. JGK extract capsule formulation complied with the assessed qualities. The JGK extract capsules can be used as a modified dosage form with increased shelf life and easy administration. The results of this study can be utilized as a reference standard for quality assurance of JGK capsules.